2018
DOI: 10.5194/hess-2018-550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contrasting rainfall-runoff characteristics of floods in Desert and Mediterranean basins

Abstract: Abstract. Catchment scale hydrological studies on drylands are lacking because of the scarcity of consistent data: observations are often available at the plot scale, but their relevance for the catchment scale remains unclear. A database of 24 years of stream gauge discharge and homogeneous high-resolution radar data over the eastern Mediterranean allows to describe the properties of moderate floods over catchments spanning from Desert to Mediterranean climates. Comparing two climatic regions, Desert and Medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The precipitation pattern can affect the spatial distribution of the susceptibility to desert fires (Tagestad et al, 2016). The precipitation threshold can control the generation of desert ephemeral streams (Kampf et al, 2018) and finally impact the runoff coefficient of desert catchments (Zoccatelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation pattern can affect the spatial distribution of the susceptibility to desert fires (Tagestad et al, 2016). The precipitation threshold can control the generation of desert ephemeral streams (Kampf et al, 2018) and finally impact the runoff coefficient of desert catchments (Zoccatelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Flash-flood conditions are frequently met in arid and semiarid regions (Nicholson, 2011;Pilgrim et al, 1988;Schick, 1988;Simmers, 2003;Tooth, 2000), as these areas are generally characterized by localized high rainfall intensities (Sharon, 1972), low precipitation interception and low infiltration rates due to sparse vegetation coverage (Danin, 1983), and exposed bedrock surfaces that are partially covered by shallow, clay-rich, undeveloped soils (Singer, 2007). Although arid and semiarid regions cover more than a third of the world's land area, knowledge of flash-flood-generating rainfall properties, hydrological response, and flood-forecasting skills in these areas is limited due to poor measurements, sparse documentation, and a relatively small number of studies (Armon et al, 2018;Nicholson, 2011;Simmers, 2003;Yang et al, 2017;Zoccatelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The former is dictated by nature, while the latter also depends on the accuracy and effectiveness of the forecasting chain. Creutin et al (2013) and Marchi et al (2010) calculated lag times for Europe under various climate regimes, and found that it increases with basin area and follows a general power-law behavior, where basins in areas smaller than 100 km 2 often had lag times of less than 1 h. Zoccatelli et al (2019) found that the mean lag time for 14 arid basins (202-1232 km 2 ) in Israel is on the order of tens of minutes to several hours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation